Astrocytoma development following complete multiple myeloma remission in a 49-year-old patient: A case report - HAN, XIAOYAN (D.A. Spandidos, 2013)
Multiple myeloma (MM), one of the B-cell non-Hodgkin lymphomas, is a bone marrow-derived, antibody-producing cancer of the plasma cells. In the advanced stages, the cancer cells frequently cause widespread osteolytic bone damage; however, in rare cases, MM also manifests as an intracranial plasmacytoma. In the present study, we describe a case in which a patient, initially treated for MM and with subsequent complete remission, was admitted to hospital with a lesion in the right cerebellar hemisphere and neurological symptoms of a brain tumor. Our initial diagnosis was an MM relapse with the rare occurring intracranial manifestation. However, pathological tests confirmed the diagnosis of a high-grade astrocytoma. In this case report, we describe the characteristics, as well as the treatment issues, diagnoses and clinical developments of this patient.